ANALISIS KEMATANGAN TATA KELOLA INFORMASI SERVICE DESK DAN INSIDEN DI YAYASAN PANGUDI LUHUR YOGYAKARTA - Suradi, Agustinus; Suyanto, M.; Amborowati, Armadyah (Universitas Respati Yogyakarta, 2013)
Improvement of service to the community demands performance, akuntanbilitas and transparency is a need for an institution, not only through the results of a product or service itself, but today are also included related service management processes. The research was conducted at the maturity analysis of the condition of the information technology governance service desk and incident.Process maturity measurement performed on the service desk and service management of the incident using COBIT 4.1 framework. Assessment is done by considering the maturity level of maturity COBIT attribute values which include: Awareness and Communication, Policies Standards and Procedures, Tools and Automation, Skill and Expertise, Responsibilities and Accountabilities, Goal setting and Measurement. IT governance maturity analysis service desk and incident using COBIT as an IT governance framework tool, with the COBIT framework generate recommendations to improve the process maturity of IT service desk and incident at the foundation so as to achieve the expected level of maturity.Â . Keywords : IT Governance, Service desk and Incident , COBIT Framework